CA19-9 as a Predictor of Worse Clinical Outcome in Medullary Thyroid Carcinoma. Issue 4 (2nd July 2019) - Alencar, Renata; Kendler, Daniel Barretto; Andrade, Fernanda; Nava, Carla; Bulzico, Daniel; Cordeiro de Noronha Pessoa, Cencita; Corbo, Rossana; Vaisman, Fernanda
Abstract : Objective: Medullary thyroid carcinoma (MTC) is a rare disease, and its classic tumor marker is calcitonin. However, recently, very aggressive cases have been reported to also secrete carbohydrate antigen 19-9 (CA19-9), and its role as a marker of worse prognosis has been questioned. The aim of this study was to analyze the relationship between CA19-9 serum levels and MTC outcomes. Methods: We retrospectively reviewed 122 MTC patients followed in a tertiary cancer center from 1985 to 2017. Clinical-pathologic characteristics, therapeutic approaches, and outcomes were recorded and CA19-9 was collected. Results: Of the 122 patients included in the study, 48 had distant metastases, and at the end of follow-up 18.1% had structural persistent disease and 32.7% had progressive disease. CA19-9 was significantly higher in those who had disease progression than in those who had not (21.4 [14.3–110.9] vs. 7.27 [0.6–44.75] U/mL, p = 0.01) and was also higher in patients who died from MTC (18.4 [14.3–110.9] vs. 7.59 [0.6–67.8] U/mL, p < 0.001). Furthermore, using a ROC curve analysis, the cutoff point for CA19-9 in MTC patients was lower than that observed in pancreatic tumors. Conclusion: CA19-9 might have a role as a prognostic factor in addition to calcitonin and carcinoembryonic antigen in metastatic MTC.